Analisis Tindak Tutur Direktif dalam Playlist “Burnout” pada Kanal YouTube Satu Persen - Nur Azizah; Nabila Agustin; Neiska Indah Nurbaeti; Sabila Rahma Desfiyanti; Fanesa Eka Nurkhakimah; Siti Aisyah; Asep Purwo Yudi Utomo; Rossi Galih Kesuma (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This research examines directive speech acts in the “Burnout” playlist on the Satu Persen YouTube channel. The aim of this research is to analyze the classification of types, contextual meanings, functions, and intentions of directive speech acts in the “Burnout” playlist on the Satu Persen YouTube channel. The research method used is a descriptive qualitative methodological approach with a pragmatic theoretical approach. Analyzing directive speech acts through comprehensive examination based on relevant theories and presenting the findings descriptively. Directive speech acts in the “Burnout” playlist include directive requestives, directive questions, directive requirements, directive prohibitives, directive permissive, and directive advisories. The research is expected to contribute to enriching pragmatic studies and expanding public awareness of pragmatics in communication. Understanding the variations in directive speech acts patterns in YouTube social media and understanding their correlation with societal realities can serve as a foundation for the public to engage more intelligently and consciously in building effective, wise, and multidimensional communication.